NILAINISASI ILMU PENGETAHUAN: KONSEP, URGENSI, DAN INTEGRASI DALAM PENDIDIKAN ISLAM - Jumiati, Dinda; Dewi, Eva; Syahrani, Amellia Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article examines the concept of the valuization of knowledge (nilainisasi ilmu pengetahuan) as an epistemological response to the crisis generated by the value-free paradigm in modern science. The study aims to analyze the nature of values in scientific knowledge, examine the challenges of globalization to the orientation of science, articulate the concept and urgency of knowledge valuization, explore the integration of knowledge and values in the Islamic tradition, and formulate applicable models of knowledge and learning integration. A qualitative approach was employed through library research, utilizing content analysis of primary and secondary sources across philosophical, epistemological, and pedagogical perspectives. The findings reveal that values are inseparable from the processes of constructing, validating, and applying scientific knowledge. Globalization presents challenges through epistemological standardization that tends to neglect the diversity of local knowledge systems while reinforcing the hegemony of Western paradigms. The Islamic tradition offers an integrative paradigm through the concept of tauhidic epistemology, bridging the dimensions of revelation and reason, as well as the spiritual and material, within a holistic framework of knowledge. The multidisciplinary, interdisciplinary, and transdisciplinary approaches to knowledge integration provide an operational framework for implementing knowledge valuization in the context of Islamic education. This study concludes that the valuization of knowledge is not merely an academic need, but an epistemological and ethical necessity in addressing the ecological, social, and existential crises confronting humanity in the contemporary era.